Die Vokale des Gesetzes: Die samaritanische Lesetradition als Textzeugin der Tora. - Schorch, Stefan (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2015)
Beside the Masoretic text, the orally transmitted Samaritan reading tradition is the most important source for the vocalisation of the Torah. The author points to parallel developments in Qumran, and sees the development of the Samaritan tradition from the 2nd century BC as part of the creation of specific group identities within Judaism, and examines its transmission. In addition, the work offers a comprehensive analysis of the more than 400 textually relevant differences in vocalisation between the Samaritan and Masoretic traditions in the Book of Genesis.